Functional Proteins Involved in Regulation of Intracellular Ca2+ for Drug Development: Role of Calcium/Calmodulin-Dependent Protein Kinases in Ischemic Neuronal Death - Shigetoshi Yano; Motohiro Morioka; Jun-ichi Kuratsu; Kohji Fukunaga (Journal of Pharmacological Sciences, 2005)
Excessive elevation of intracellular calcium level seems to be a trigger of ischemic neuronal injury. Calcium/calmodulin (CaM)-dependent protein kinase kinase (CaM-KK) is an upstream kinase for CaM kinase IV (CaM-KIV) that was reported to prevent apoptosis through phosphorylation of CREB (cyclic AMP responsive element-binding protein). We here observed that CaM-KK could directly activate Akt, thereby preventing apoptosis in cultured cells. Then we examined changes in Akt and CaM-KIV activities in gerbil forebrain ischemia. In 5-minischemia-caused delayed neuronal death in hippocampal CA1 neurons, Akt and CaM-KIV activities were decreased after reperfusion. On the other hand, during induction of ischemic tolerance, Akt activity gradually and persistently increased in the CA1 neurons with transient increase in CREB phosphorylation. Inhibition of Akt activity with wortmannin or CREB-DNA binding with CRE-decoy injection resulted in failure of generation of ischemic tolerance. These results indicated activation of Akt and CaM-KIV play important roles in induction of the ischemic tolerance. Activation of CaM-KK may provide a new strategy for overcoming the ischemic stress. Keywords:: Ca2+/calmodulin-dependent protein kinase kinase, Akt, CREB, cerebral ischemia, tolerance